(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The aim of this article is to present the classification of vowels in A. Baitursynuly`s work. He is a founder of Kazakh linguistics. А. Baitursynuly is a reformer who presented new sample and national alphabet in the history of Kazakh science. Оku kuraly (1912) is one of the first alphabet written by A. Baitursynuly in Kazakh language. This alphabet was rewritten from the point of new methodologies of teaching and republished several times until 1925. А. Baitursynuly is a scientist linguist. He reformed Kazakh alphabet on the basis of Arabic script. Founder of the first Kazakh alphabet Akhmet Baitursynuly wrote «Alphabet is a paradise of signs dedicated to the basic sounds of language. Resources of these signs for language and its sounds are sufficient enough, it coincides with the sounds or with its help it will be easy to read, write and learn, if it is suitable to use in the means of art, alphabet would be better». Sounds, vowels and classification of vowels in A. Baitursynuly`s works are considered in this article.